A variance decomposition of index-linked bond returns - Francis Breedon (Queen Mary University of London, School of Economics and Finance, 2012)
We undertake a variance decomposition of index-linked bond returns for the US, UK and Iceland. In all cases, news about future excess returns is the key driver though only for Icelandic bonds are returns independent of inflation.
Keywords: E43; G12; 330; index-linked bonds; variance decomposition; real interest rate